Regional Participation in the Maintenance of International Peace and Security under the UN Charter: The Case of African Union and its Sub-Regional Organisations - Chakanyuka, Tatenda Leopold (Kathmandu School of Law Review, 2024)
Under Chapter VIII of the UN Charter, the African Union shares the responsibility of maintaining international peace and security and finding African solutions in addressing conflicts on the African continent. Article 52 allows for the setting up of regional organisations to complement the work of the UN, especially in the peaceful settlement of disputes in terms of the Charter. Article 53 establishes a working relationship between regional organisations and the Security Council when it comes to the use of force. The operations of the regional organisations in terms of use of force are directly linked with the Security Council as they cannot act independently of the Security Council. While the Security Council can utilise the regional organisations in peace enforcement, the regional organisations cannot act outside of the UN Charter. On the one hand, the Security Council has neglected conflicts in Africa. On the other hand, it has significantly interfered with the efforts of the region to promote peace and security. There is a need to enhance and reinterpret Chapter VIII on regional arrangements for lasting solutions to be found. The Security Council must be able to take note and pay much attention to views coming from the regional organisations that are closer and with a deep understanding of the on the ground situation. Greater, constant communication channels between the Security Council and the regional organisation must be opened. The African Union should also utilise presently available avenues under the UN Charter to push for greater participation in the maintenance of international peace and security and must enhance its capacity to deal with peace and security issues on the continent.